Impact of nitrogen and sulphur fertilizer rates on nitrogen uptake dynamics and nutrient use efficiency in wheat - Sai, G P; Singh, A; Sarkar, S; Sana, Z A; Pallavi; Chakraborty, A; Fatima, I (Plant Science Today, 2025)
A field experiment was performed to assess the impact of nitrogen (N) and sulphur (S) fertilizer rates, along with their interactions, on nutrient uptake, content and nitrogen use efficiency (NUE) in wheat at various growth stages. The study examined the effects of administering 40 kg N, 80 kg N, and 120 kg N alongside 0 kg S, 15 kg S, and 30 kg S on N and S uptake, as well as grain and shoot nutrient content during wheat ontogeny. Nitrogen uptake and concentration in wheat grain and shoots were significantly increased by 120 kg of N and 30 kg of S. At 120 kg N + 30 kg S, shoots (13.91, 34.80, 41.50 and 39.89 kg/ha) and grains (152.36 kg/ha) showed the highest uptake, with the lowest recorded in the control. Sulphur uptake followed a similar pattern, peaking at 120 kg N + 30 kg S (3.17, 6.91, and 8.36 kg/ha) in the shoots. This treatment had the highest S levels in shoots (0.67%, 0.44%, and 0.34%) and grain (0.288%) compared to the control group. The 120 kg N + 30 kg S treatment had the highest NUE and sulphur use efficiency (SUE) (91.31% and 84.10%, respectively), while the 40 kg N + 0 kg S and 40 kg N + 15 kg S treatments recorded the lowest values (53.14% and 11.03%). Nitrogen production efficiency peaked at 21.187 kg yield/kg N at 120 kg N and 0 kg S, but S production efficiency decreased with higher S levels. Balancing N and S improved nutrient absorption, content, and utilization efficiency in the wheat production system.